2020
DOI: 10.1111/1348-0421.12799
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the minimum region of Bordetella pertussis Vag8 required for interaction with C1 inhibitor

Abstract: An autotransporter of Bordetella pertussis , virulence‐associated gene 8 (Vag8), binds and inactivates the complement regulator, C1 inhibitor (C1‐Inh), and plays a role in evasion of the complement system. However, the molecular interaction between Vag8 and C1‐Inh remains unclear. Here, we localized the minimum region of Vag8 required for interaction with C1‐Inh by examining the differently truncated Vag8 derivatives for the ability to bind and inactivate C1‐Inh. The truncated Vag8 conta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…5D ). In addition, the truncated fragment of Vag8 ranging from amino acid positions 102 to 479 (ΔC479), which is unable to bind and inactivate C1-Inh, did not increase the number of coughs in mice inoculated with LOS and PTx; in contrast, other types of truncated Vag8, which retain the ability to inhibit C1-Inh increased the number of coughs, similar to Vag8 ( 49 ) ( Fig. 5E to G ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…5D ). In addition, the truncated fragment of Vag8 ranging from amino acid positions 102 to 479 (ΔC479), which is unable to bind and inactivate C1-Inh, did not increase the number of coughs in mice inoculated with LOS and PTx; in contrast, other types of truncated Vag8, which retain the ability to inhibit C1-Inh increased the number of coughs, similar to Vag8 ( 49 ) ( Fig. 5E to G ).…”
Section: Resultsmentioning
confidence: 96%
“…The expression vectors for histone acetyltransferase (HAT)-tagged recombinant Vag8 proteins, pCold II-HAT- vag8 Tohama and pCold II-HAT- vag8 18323 , and pCold II-HAT- vag8 102–596, 102–548, and 102–479 , which were constructed as previously described ( 49 ), were introduced into E. coli BL21(DE3). The Vag8 proteins were expressed by incubation at 15°C for 24 h in the presence of 1 mM isopropyl-β- d -thiogalactopyranoside (IPTG).…”
Section: Methodsmentioning
confidence: 99%
“…The passenger domain of Vag8 (Vag8 p ) is cleaved and liberated into the extracellular milieu 8,9 . The liberated Vag8 inactivates C1 inhibitor, which negatively regulates bradykinin generation in the kallikrein–kinin system, to upregulate bradykinin levels, resulting in exacerbation of the cough response 6,10 . In the present study, we investigated the protective effects of immunization with the Vag8 p against B. pertussis –induced coughing in mice.…”
Section: Figurementioning
confidence: 99%
“…The recombinant proteins were expressed in Escherichia coli DH5α or BL21 (DE3) and purified by nickel affinity chromatography as described previously. 10 We intraperitoneally injected mice with recombinant proteins (0.15, 1.5, or 15 µg/mouse) in combination with 1/25th the human dose of DPT-IPV or alum (2 mg) and assessed the cough production and the bacterial colonization of the tracheas and lungs after the intranasal inoculation of B. pertussis 18323 on the same schedule as described earlier. We confirmed the production of anti-Vag8, anti-Phg, and anti-SphB2 IgG antibodies in Vag8 p -, Phg-, and SphB2-immunized mice, respectively, by ELISA 3 (Figure 2a) and observed that immunization with Vag8 p did not affect the levels of anti-PTx IgG antibody in DPT-IPV-immunized mice (Figure 2b).…”
mentioning
confidence: 99%
See 1 more Smart Citation